A Quantitative Model of Instructional Leadership and Job Satisfaction: Regression-Based Evidence from Private Primary Schools in China - Liu, Xiaohan; Hamid, Aida Hanim A.; Nor, Mohamed Yusoff Mohd (PT Mattawang Mediatama Solution, 2025)
Teacher job satisfaction is essential for ensuring high-quality education. While instructional leadership and teacher professional development are widely recognized as influential factors, their interaction remains insufficiently examined, particularly in the context of private primary schools in China. This study investigates how headteachers’ instructional leadership and teachers’ professional development contribute to job satisfaction, using data collected from 350 teachers in private primary schools in Zhengzhou, China. Regression and mediation analyses were conducted with SPSS and PROCESS to assess the direct and indirect relationships among the variables. The findings reveal that both instructional leadership and professional development positively influence teacher satisfaction. Furthermore, teacher professional development partially mediates the effect of instructional leadership on job satisfaction, indicating a dual pathway through which school leaders can enhance outcomes for teachers. These results underscore the importance of supportive leadership and continuous professional opportunities in fostering a satisfied and motivated teaching workforce. The study contributes to the growing body of applied educational research in non-Western contexts and offers practical implications for improving teacher retention and development practices in private education settings.